Pengaruh Literasi Keuangan, Sikap Keuangan Dan Locus Of Control Terhadap Perilaku Konsumtif Mahasiswa PenerimaKip Kuliah Fakultas Ekonomi Universitas Nuku Kota Tidore Kepuluan - Ohorella, Eka Chrisma Rahmawaty; Hasan, Muhammad Hi.; Ruray, Titiek Arafiani (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to determine and analyze the influence of Financial Literacy, Financial Attitude, and Locus of Control on the Consumer Behavior of KIP Kuliah recipients from the Faculty of Economics at Nuku University in Tidore Islands City. This research is quantitative research using primary data obtained from the distribution of questionnaires, which were then measured using a five-point Likert scale. The research sample consisted of 95 students receiving KIP Kuliah scholarships. The data analysis method used was Multiple Linear Regression Analysis with the assistance of Statistical Package for Social Science (SPSS) software. The research results show that: 1) Financial literacy, financial attitude, and locus of control simultaneously have a significant effect on the consumer behavior of students receiving KIP Kuliah at the Faculty of Economics, Universitas Nuku, Kota Tidore Kepulauan. 2) Financial literacy partially has no and is not significant effect on the consumer behavior of students receiving KIP Kuliah at the Faculty of Economics, Universitas Nuku, Kota Tidore Kepulauan. 3) Financial attitude partially has no and is not significant effect on the consumer behavior of students receiving KIP Kuliah at the Faculty of Economics, Universitas Nuku, Kota Tidore Kepulauan. 4) Locus of control partially has a significant effect on the consumer behavior of students receiving KIP Kuliah at the Faculty of Economics, Universitas Nuku, Kota Tidore Kepulauan.